Optimisasi Pembelajaran Online di MTS Al Falah menggunakan Node.js Express dan MongoDB - Hendri (Jurnal PROCESSOR, 2023)
E-Learning is an approach to developing knowledge, skills, and competencies through internet technology-based facilities. E-Learning allows teaching materials to be conveyed to students via the internet, intranet or other computer network media. Mts Al Falah Pancuran is a school located in a remote area on the border between Jambi province and South Sumatra province. In this area there is no internet network so that it attacks teachers in finding references to make material as learning materials and challenges students to find references for learning. Build a web-based E-Learning application and implement it using the Nodejs web programming language, for database management using mongodb and its creation using the waterfall method which includes analysis, design, implementation and testing. From the results of the analysis and interviews the researcher tried to apply the web-based E-Learning concept by making one of the existing computers a server for the E-Learning application using a Local Area Network (LAN) network, so that the application can still be accessed even without an internet network because the application is running. On a computer that has functioned as a server and accessed by client computers in the same network.